2001
DOI: 10.4141/a01-040
|View full text |Cite
|
Sign up to set email alerts
|

Influence of condensed tannins on gut morphology in sheep fed Lotus pedunculatus

Abstract: can reduce intestinal absorption of amino acids (AA) and peptides. This experiment tested the hypothesis that CT in Lotus pedunculatus altered small intestinal mucosal morphology reducing absorptive capacity of the gut. Thirteen young Romney wethers were fed ad libitum either Lotus pedunculatus (cv. Grasslands Maku, N = 7) containing 5.5% CT in the dry matter (DM) or white cloverperennial ryegrass pasture (N = 6), which did not contain CT, for 4 wk. The wethers were euthanized at the end of the feeding trial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…However, there were no morphological changes in the duodenum, possibly due to the alkaline environment of the jejunum and ileum (Wang et al 1996;Dawson et al 1999). Similar levels of CT present in fresh Lotus pedunculatus (5.5% CT) had no effect on the morphology of the duodenum, jejunum or ileum in lambs (Walton et al 2001). This suggests that various types of CT may differ in their effects on FSR within the digestive tract as well as on animal production, due to variations in their chemical structure (Aerts et al 1999).…”
Section: Discussionmentioning
confidence: 98%
“…However, there were no morphological changes in the duodenum, possibly due to the alkaline environment of the jejunum and ileum (Wang et al 1996;Dawson et al 1999). Similar levels of CT present in fresh Lotus pedunculatus (5.5% CT) had no effect on the morphology of the duodenum, jejunum or ileum in lambs (Walton et al 2001). This suggests that various types of CT may differ in their effects on FSR within the digestive tract as well as on animal production, due to variations in their chemical structure (Aerts et al 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Decreased voluntary feed intake may be associated with astringency caused by the formation of tannin-salivary protein complexes in the mouth or signals of gut distension resulting from tannin interactions with proteins of the gut wall (D'Mello & Devendra, 1995). Tannins may also inhibit gut enzyme activity and affect gut permeability, causing decreased passage of nutrients through the gut wall (Walton et al 2001). N balance studies have demonstrated an increase in faecal N, often ascribed to undigested complexes between tannins and feed or microbial N. However, in some cases faecal N content is greater than N availability in the feed, and Barry (1989) has suggested a compensatory tannin-induced increase in microbial growth.…”
Section: Tanninsmentioning
confidence: 99%
“…Also there have been findings indicating a trend of decreasing villus height and villus surface area in the proximal duodenum [5]. Conflicting reports on the effects of tannins on the morphometry of the intestine have been attributed to differences in species and to the site of sampling due to the wide variations in intestinal structure along the digestive tract [6].…”
Section: Discussionmentioning
confidence: 98%
“…There was an indication of these classical effects of tannin-containing feeds in ruminants from a digestibility trial using UTPF with sheep [3]. Higher levels of nitrogen in the faeces indicate lower nitrogen retention, which is a characteristic of dietary tannins, which bind to proteins in the rumen and consequently reduce digestion and absorption in the gut [2,4,5]. There are also reports that tannins may form complexes with carbohydrates and minerals and consequently inhibit microbial and digestive processes in ruminant animals, resulting in depressed rumen digestive function [2,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation